Phenotypic correlations between growth characteristics in juveniles of common snook, Centropomus undecimalis - Filho, João Costa; de Mello, Giovanni Lemos (Arquivos de Ciências do Mar, 2015)
The knowledge of biometric parameters provides information applicable to cultivation of species with potential for  aquaculture, such as common snook,  Centropomus undecimalis . Thus, the aim of this study was to develop in a  population of juvenile common snook a series of biometric parameters and statistically analyze the phenotypic correlation  between the data obtained. Biometry was performed in 151 juvenile common snook and collected data were analyzed using  SAS for estimation of descriptive statistics and correlations between parameters. The phenotypic correlations between  parameters height, head length, standard length, total length, pre-dorsal length, width and body weight indicated these  characteristics are strongly associated and has a higher interest in selection program based on the phenotype of individuals.  The results of this study provide biometric reference values  for juvenile common snook, contributing to the monitoring  and evaluation of growth characteristics in culture conditions, which may serve as a basis for structuring a breeding  program for this species.